Restructuring National Defense Policy through the Integration of Artificial Intelligence for Strategic Decision-Making - M. Taher AM; Joni Widjayanto; Rodon Pedrason; Robby M. Taufiq; Asep Adang Supriyadi (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid development of artificial intelligence (AI) has changed the strategic environment of national defense by increasing the speed, volume, and complexity of information that must be processed before policy and operational decisions are made. This article analyzes how AI can be integrated into national defense policy as a strategic decision-support capability while maintaining legal, ethical, and institutional control. Using a qualitative literature study and policy analysis, the article synthesizes peer-reviewed studies, defense policy documents, and responsible-AI governance frameworks published between 2018 and 2024. The analysis shows that AI can strengthen defense decision-making through intelligence data fusion, predictive threat assessment, cyber defense, logistics optimization, command-and-control support, and military training simulation. However, AI integration also creates risks related to algorithmic bias, data security, accountability, human oversight, interoperability, technological dependence, and uneven institutional readiness. The article proposes a policy reformulation model based on six pillars: clear legal mandate, responsible AI governance, secure data and digital infrastructure, human-AI teaming, accountable acquisition and testing, and cross-sector collaboration. The study concludes that AI should not be positioned as a replacement for commanders or policymakers, but as a controlled decision-support instrument that improves the quality and timeliness of strategic choices. A defense policy that combines technological innovation with human judgment, ethical safeguards, and institutional resilience is essential for strengthening national defense in an increasingly complex security environment.